Platelet Reactivity in Unstable Coronary Artery Disease - Swahn, Eva; Wallentin, Lars (Thrombosis and Haemostasis, 1987)
Unstable coronary artery disease (CAD) might be related to obstructions of coronary blood flow by platelet aggregates. In 121 men and 43 women admitted to the coronary care unit with suspected unstable CAD, blood samples for tests of platelet function were obtained within 24 hours after admission. Platelet reactivity was tested in vitro in platelet rich plasma as the aggregability towards ADP 1 μM and collagen 1 mg/ml and as the sensitivity to prostacyclin (PSP). The levels of beta-thrombo-globulin and platelet factor 4 were determined ex vivo in platelet poor plasma. Patients who developed a nontransmural myocardial infarction (n = 39) or had signs of myocardial ischemia at an exercise test performed within a week (n = 39) were considered to have unstable CAD while patients without signs of ischemia constituted the control group. In the acute phase the PSP was reduced in patients with unstable CAD without any difference between genders. The aggregability towards ADP was higher in women than men but otherwise there were no differences between groups or sexes in any other test in the acute phase. After 12 months there were no differences in PSP between the groups but women had a lower PSP than men. Thus, in the acute phase of unstable CAD, the platelet sensitivity to the inhibitory effects of prostacyclin was reduced which might contribute to the risk for further platelet aggregation, coronary occlusion and myocardial infarction.
Keywords: Unstable coronary artery disease; Nontransmural myocardial infarction; Exercise test; Platelet aggregation; Platelet sensitivity to prostacyclin; Beta-thromboglobulin; Platelet factor 4